Analysis of Intersectoral Collaboration Level in Health Informatics Studies - İlker Köse; Şeyma Güner; Ayşe Elif Yıldız; Enise Topaylı (Association of Nurse Managers, 2023)
Aim: The aim of the study is to reveal the level of cooperation in health informatics practices. Method: In order to reach the aim of the study by determining the level of cooperation between sectors in health informatics studies, the extent of research on the theme of ''health informatics'' in health quality and performance congresses was examined. As a data source, academic studies published at various congresses held between 2009 and 2021 were analyzed. In accordance with the main purpose of the study, document analysis, which is a qualitative research method was carried out in the congress proceedings booklets. Results: According to the findings, it was seen that 66.1% of the academic studies in the field of health informatics were carried out only by university employees, while the rate of studies conducted in university-public cooperation was 16.1%. In addition, it was concluded that the work carried out by the employees of the Ministry of Health has a rate of 10.7%. While only 1.80% of the studies were carried out by private sector employees, it was observed that similarly, studies created through university-private sector cooperation constitute 1.80% of all studies. It has been seen that publications prepared in cooperation with the public-private sector constitute 0.90% of all publications, while publications prepared in cooperation with the university-other public sector constitute 0.90% of all publications at the same rate. Conclusion: The results of the study show that the level of cooperation is not sufficient, considering the importance of cooperation and the benefits that can be obtained from work done in cooperation. In this context, the study emphasizes the need to increase the encouragement of cooperation between health service providers in the field of health informatics and offers suggestions in this regard.